Limited utility of plasma elafin as a biomarker for skin graft‐versus‐host disease following allogeneic stem cell transplantation. (1st December 2021) - George, L.; Mahabal, G.; Mohanan, E.; Balasubramanian, P.; Peter, D.; Pulimood, S.; Lakshmi, K.; Jeyaseelan, L.; Abraham, A.; Srivastava, A.; Mathews, V.; George, B.
Summary: Background: Acute cutaneous graft‐versus‐host disease (acGVHD) following haematopoietic stem cell transplant (HSCT) is common but difficult to distinguish from other causes of rash. Plasma elafin has been proposed as a diagnostic and prognostic biomarker of skin GVHD. Aim: To evaluate the role of plasma elafin as a biomarker in acGVHD in an Indian population. Methods: Plasma elafin was evaluated in a prospective study of HSCT recipients, conducted over 2 years, taking measurements at baseline and at onset of skin rash after HSCT. Patients were categorized into those with GVHD rash, those with non‐GVHD rash and those with no rash and the three groups were compared. Results: Two hundred and sixty‐one patients with a median age of 16 years (range 1–61 years) and a male predominance (175 : 86 M/F) underwent HSCT during the study period: 56 patients in the GVHD group, 49 in the non‐GVHD group and 156 in the no‐rash group. The median baseline elafin was similar in all three groups. At the onset of rash, median elafin level was similar between GVHD and non‐GVHD rash (34 549 vs. 32 077 pg/mL; P = 0.58) and between GVHD and no rash (34 549 vs. 26 197 pg/mL; P = 0.08). A rise in elafin from baseline was significantly different between GVHD and no rash ( P < 0.001) but not between GVHD and non‐GVHD rash ( P = 0.44). Conclusion: The utility of plasma elafin as a biomarker of skin GVHD is very limited. Plasma elafin, although elevated in cutaneous GVHD, is not helpful in distinguishing between GVHD rash and other causes of rash following HSCT.